2020
DOI: 10.1055/s-0040-1712132
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Health-related Behaviors in Gestational Weight Gain among Women with Overweight and Obesity: A Cross-sectional Analysis

Abstract: Objective To evaluate the influence of health-related behaviors including food intake, physical activity, sleep time, smoking habits, stress, depression, and optimism on excessive gestational weight gain (GWG) among women with overweight and obesity. Methods A cross-sectional study was conducted at the Women's Hospital of the Universidade de Campinas, Campinas, state of São Paulo, Brazil, with 386 mediate postpartum women that fit the inclusion criteria of ≥ 19 years old, first prenatal care visit at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
1
6
0
5
Order By: Relevance
“…Other factors identified in this review regarding gestational weight gain were socioeconomic status, 3,15,19 maternal age over 20 years, 17,19 parity, 17,21 and others were identified in only one study, such as smoking, 19 work, 2 schooling, 14 stress, 18 single fetus, 19 neighborhood violence, 20 planned weight gain above guidelines. 21 Table 1 also shows the quality assessment of the studies performed using the JBI "JBI Critical Appraisal Checklist", in which they were classified as low and moderate risk of bias.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Other factors identified in this review regarding gestational weight gain were socioeconomic status, 3,15,19 maternal age over 20 years, 17,19 parity, 17,21 and others were identified in only one study, such as smoking, 19 work, 2 schooling, 14 stress, 18 single fetus, 19 neighborhood violence, 20 planned weight gain above guidelines. 21 Table 1 also shows the quality assessment of the studies performed using the JBI "JBI Critical Appraisal Checklist", in which they were classified as low and moderate risk of bias.…”
Section: Resultsmentioning
confidence: 87%
“…20 Most of the selected studies were produced in the USA 14,16,19,20 and Brazil. 2,3,17,18 Among the studies analyzed, the factor that was present in a greater number of articles was weight during the prepregnancy period. 3,[14][15][16][17]19,21 Pregnant women who were overweight or obese before pregnancy were more likely to have high weight gain compared to eutrophic pregnant women.…”
Section: Resultsmentioning
confidence: 99%
“…Há estudos que relacionam o estresse e o menor período do sono como fatores favoráveis ao ganho de peso gestacional excessivo. O mesmo foi evidenciado nos ensaios clínicos analisados, apesar de que mais estudos devem ser realizados para esclarecer essa relação (KOMINIAREK et al, 2018;PAULINO et al, 2020).…”
Section: Discussionunclassified
“…[12][13][14][15][16][17] In non-pregnant populations, poor sleep health indicators such as short or long sleep duration, early or late sleep timing, low sleep efficiency (a measure of continuous vs. interrupted sleep), and low sleep regularity across days are independently associated with obesity and weight gain. 18 Among the few studies examining associations between sleep and GWG, most, [19][20][21] but not all, 22 studies have found short sleep duration and perceived sleep deprivation to be associated with increased risk of low GWG (i.e., less than NAM guidelines).…”
Section: Synopsismentioning
confidence: 99%
“…Our findings that individuals’ sleep domains were not associated with GWG are consistent with the findings of some literature but conflict with others. 1922, 46, 47 For example, Abeysena et al examined associations of self-reported sleep duration in the second and third trimesters and found sleeping <8 h/day (vs. >8 h/day) during the second, third, or both second and third trimesters was associated with higher odds of the IOM defined inadequate GWG (OR 1.60, 95% CI 1.05, 2.46) adjusting for the effect of body mass index and gestational age. 19 Likewise, Hill et al found that short sleep duration in late pregnancy was associated with higher odds of inadequate GWG (1.39; 1.03–1.87) and inversely associated with gestational fat gain (−0.36 – 0.16 0.02).…”
Section: Commentmentioning
confidence: 99%